2012
DOI: 10.1021/je201055w
|View full text |Cite
|
Sign up to set email alerts
|

A Functionalized High-Surface-Energy Ammonium-Based Ionic Liquid: Experimental Measurement of Viscosity, Density, and Surface Tension of (2-Hydroxyethyl)ammonium Formate

Abstract: The ammonium-based ionic liquid (2hydroxyethyl)ammonium formate has been known for ease of synthesis and great solvation properties. In this work, this ionic liquid was synthesized, and its temperature-dependent density, surface tension, and viscosity were measured. Surface tension was measured by the capillary rise method using a homemade capillary apparatus in which the liquid and vapor can be brought into equilibrium. Measurements of viscosity and surface tension were performed under a water-vapor-free atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
4
25
1
Order By: Relevance
“…The results presented in Table 1 These differences can be related to the different purities (water or unreacted chemicals) of the used ionic liquids. However, the experimental results determined in this work are similar to the reported by Ghatee et al [41]. These studies are important because there is a lack of accuracy of the most common reported methods and a limited range of temperatures are studied which is a barrier for the industrial application of ionic liquids.…”
Section: Characterization Of Protic Ionic Liquidssupporting
confidence: 89%
“…The results presented in Table 1 These differences can be related to the different purities (water or unreacted chemicals) of the used ionic liquids. However, the experimental results determined in this work are similar to the reported by Ghatee et al [41]. These studies are important because there is a lack of accuracy of the most common reported methods and a limited range of temperatures are studied which is a barrier for the industrial application of ionic liquids.…”
Section: Characterization Of Protic Ionic Liquidssupporting
confidence: 89%
“…[20][21][22][23] However, these fitting parameters reveal no insight into which molecular-level variables influence transport phenomena. Here we use the CAF to demonstrate that the temperature dependence of mass and charge transport in molten salts can be very accurately described using only system properties instead of empirical equations.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to report not only new measurements for density data of 2-HEAF but also molecular dynamic considerations, for which only one effort has been yet reported only under ambient condition [21]. The experimental results for the atmospheric densities (at 0.1 MPa) are going to be compared with the previously reported measurements [16,24]. In addition the mechanical coefficients of 2-HEAF are calculated by the use of a Tait-type equation to derive the internal pressure of IL of interest.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An extensive literature survey of the previous efforts is available in the recent work of Hosseini et al [21]. The atmospheric densities of 2-HEAF have yet been measured by the use of several apparatuses from non-digital ones like pycnometer [16] to those were based on the digital apparatus like vibrating-tube densimeter [17,[22][23][24].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation